Effects of drying conditions on the technological properties of sheet natural rubber - Jayasuriya M M; Kumara G; Kurupu C...; Liyanage R; Mitrananda K M U; Ratnayake U; Siriwardena S; Yapa S (Journal of Rubber Research, 2000)
Attempts were made to prepare natural rubber sheets by varying the drying time and drying conditions. Rheological and technological properties of rubber compounds based on ACS-1 and tread formula were evaluated. It was found that sun drying of rubber sheets for up to 2 days, followed by smoking for up to 2 days could impact equivalent physical properties with that of purely smoked rubber. In addition, it was found that drying of rubber sheets under sunlight for 2-4 days did not impart inferior physical properties.
Keywords: Dry rubber content; Drying; Sheet natural rubber